2006
DOI: 10.1073/pnas.0602567103
|View full text |Cite
|
Sign up to set email alerts
|

Progression of prostate cancer by synergy of AKT with genotropic and nongenotropic actions of the androgen receptor

Abstract: Classic work by Huggins and Hodges demonstrated that human prostate cancer regresses dramatically during antihormonal therapy but recurs frequently with androgen independence. Perturbations in the androgen receptor (AR) and PTEN-AKT signaling axes are significantly correlated with the progression of prostate cancer. Genetic alterations of the AR cause receptor hypersensitivity, promiscuity, and androgen-independent receptor transactivation. Prostate cancers maintain an elevated AKT activity through the loss of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
143
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 151 publications
(155 citation statements)
references
References 36 publications
11
143
1
Order By: Relevance
“…(29) and results in activation of the PI3K pathway. We demonstrated that increased PI3K signaling via shRNA-mediated PTEN knockdown or overexpression of an activated form of AKT in murine prostate cells causes PIN lesions in the tissue-regeneration model (30,31). In this study, we combined overexpression of ERG and activated AKT and found that grafts derived from coinfected adult prostate cells weighed 2-3 times more than grafts generated from AKT or ERG overexpression alone (Fig.…”
Section: Combined Erg Overexpression and P53 Deletion In Prostate Epimentioning
confidence: 69%
“…(29) and results in activation of the PI3K pathway. We demonstrated that increased PI3K signaling via shRNA-mediated PTEN knockdown or overexpression of an activated form of AKT in murine prostate cells causes PIN lesions in the tissue-regeneration model (30,31). In this study, we combined overexpression of ERG and activated AKT and found that grafts derived from coinfected adult prostate cells weighed 2-3 times more than grafts generated from AKT or ERG overexpression alone (Fig.…”
Section: Combined Erg Overexpression and P53 Deletion In Prostate Epimentioning
confidence: 69%
“…Alterations in androgen receptor signaling causing receptor hypersensitivity, promiscuity, or androgen-independent receptor trans-activation are also a common feature of prostate cancer . When additional AR is introduced in addition to constitutively active AKT, regenerated grafts contain androgen-independent adenocarcinoma, resembling what is seen in the human disease (Xin et al 2006).…”
Section: Human Prostate Cancer and Prostate Cancer Modelsmentioning
confidence: 84%
“…AR has been shown in prostate cancer epithelial cells to influence the expression levels and activities of several cell-cycle genes essential for the G 1 -S and G 2 -M cell-cycle transition (40,47). In addition, Akt regulates the expression and stability of AR at multiple levels, ranging from transcriptional to posttranslational modulation (48). We, therefore, hypothesized that AR and p-Akt may regulate the expression of cyclin B1 together.…”
Section: Discussionmentioning
confidence: 99%